2020
DOI: 10.1002/acr.24056
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation, Management, and Long‐Term Outcome of Pars Planitis, Panuveitis, and Vogt‐Koyanagi‐Harada Disease in Children and Adolescents

Abstract: Objective. Chronic uveitis is a common manifestation of pediatric rheumatologic conditions and may result in irreversible blindness and long-term disability. While chronic anterior uveitis is the most commonly encountered ocular manifestation of rheumatic disease, little is known about the clinical presentation, management, and long-term outcome of more complex eye conditions such as pars planitis (PP), panuveitis (PU), and Vogt-Koyanagi-Harada disease (VKH). The present study was undertaken to comprehensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Further, 37% experienced one or more ocular complications, and over 40% had visual impairment during their disease course. In general, children with non‐anterior uveitis tend to have worse visual outcomes (33,34). In our cohort there were higher rates of visual impairment, ocular complications, and topical glucocorticoid use in patients with other uveitis compared to JIA‐U.…”
Section: Discussionmentioning
confidence: 99%
“…Further, 37% experienced one or more ocular complications, and over 40% had visual impairment during their disease course. In general, children with non‐anterior uveitis tend to have worse visual outcomes (33,34). In our cohort there were higher rates of visual impairment, ocular complications, and topical glucocorticoid use in patients with other uveitis compared to JIA‐U.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, many VKH patients do not receive proper treatment, instead receiving delayed or inadequate therapy (suboptimal medication, premature tapering of medication or absence of immunosuppressants), and the disease inevitably progresses to the chronic recurrent stage, in which granulomatous ocular inflammation recurs and most ocular complications emerge, including complicated cataract, secondary glaucoma, choroidal neovascularization, subretinal fibrosis and others (17,(22)(23)(24). It has been indicated that ∼21% of VKH patients become legally blind (25).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al reported the presence of neurological disease to the extent of 7.9% in a large series of patients with uveitis in whom 1.1% cases were of VKH disease and 1.0% of multiple sclerosis [10]. In a study by Reiff et al to assess the long term safety and efficacy of disease-modifying antirheumatic drugs (DMARDs) and biologics for treatment of paediatric and adolescent patients with pars planitis (PP), panuveitis (PU) and VKHD, they found 98% of patients required additional DMARDs and 73% required therapy with biologics.At the end of study 35% patients across all groups had significant visual loss or were blind.They concluded that as all three groups involve a high risk of permanent visual loss they should be managed by skilled rheumatologist early and aggressively [11]. In another study by Albaroudi et al on paediatic VKHD, they concluded that life expectancy justifies early initiation of immunesuppressive or even biological therapy to achieve better steroid sparing and most importantly preserve visual function [12].…”
Section: Discussionmentioning
confidence: 99%